Additional calcar support using a blade device reduces secondary varus displacement following reconstruction of the proximal humerus: a prospective study. Issue 1 (December 2015) - Beirer, Marc; Crönlein, Moritz; Venjakob, Arne; Saier, Tim; Schmitt-Sody, Marcus; Huber-Wagner, Stefan; Biberthaler, Peter; Kirchhoff, Chlodwig
Abstract Background Locking plate fixation of displaced fractures of the proximal humerus is still accompanied by a distinct complication rate, especially in case of osteoporotic bone, short-segment fracture length and comminution of the medial calcar. Secondary loss of reduction leading to varus deformity and screw cutout most frequently lead to surgical revision. The aim of the present study was to evaluate the clinical and radiological outcome of a recently developed polyaxial locking plate that allows for the additional placement of a helical blade device, aiming for support of the medial calcar. Methods In this prospective study, 17 patients with a mean age of 63.0 ± 16.0 years suffering from displaced fractures of the proximal humerus (Neer type two-, three- and four-part) were enrolled. All patients were surgically treated using a polyaxial locking plate with additional blade device (group PAB, n = 12) or without blade device (group PA, n = 5). Functional outcome was recorded using the Munich Shoulder Questionnaire allowing for qualitative self-assessment of the Shoulder Pain and Disability Index (SPADI), the Disability of the Arm, Shoulder and Hand (DASH score) and the Constant Score. Radiological outcome was assessed by analyzing standardized true anterior–posterior and outlet-view radiographs with respect to radiographic evidence of secondary varus displacement, cutout of screws and hardware failure. Results were compared to an age-, gender- and fracture type-matched collective treated by monoaxial locking plate fixation (group MA, n = 15). Results The mean follow-up was 12.4 ± 2.9 months after surgery. There were no statistical significant differences in clinical outcome in all three groups. Group MA and group PA revealed significant secondary varus displacement in comparison to group PAB at the final follow-up compared to postoperative analysis (p < 0.001). The distance between the blade and the articular surface showed no significant increase in group PAB at the final follow-up compared to postoperative analysis. Not-implant-related complications were seen in one and implant-related complications were seen in two patients in group PAB. Conclusions Polyaxial locking plate fixation with a blade device to restore medial cortical support reduces the risk of secondary varus displacement even in proximal humeral fractures of the elderly in comparison to monoaxial and polyaxial locking plate fixation without blade insertion.